BEYOND THE PROMOTION OF ECONOMIC COOPERATION: THE ECONOMIC COMMUNITY OF WEST AFRICAN STATES PEACEKEEPING INVOLVEMENTS IN WEST AFRICA - ugo chuks okolie; Ejogba Abraham ORHERO (Universitas 17 Agustus 1945 Jakarta, 2023)
In order to raise the living standards of its people, maintain and improve economic stability, foster relations among Member States, and contribute to the advancement and development of the African continent, Economic Community of West African States (ECOWAS) was established. Its goal is to promote cooperation and integration that will result in the creation of an economic union in West Africa. According to a set of guiding principles, such as impartiality, the parties' consent, and the non-use of force unless necessary for self-defense, a third party intervention known as